2015
DOI: 10.4238/2015.february.13.15
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of microsatellite and single nucleotide polymorphism markers for parentage analysis in European domestic pigs

Abstract: ABSTRACT. Parentage analysis and individual identification are recent, promising methods that have been applied to evolutionary and ecological studies, as well as conservation management. Parental exclusion relying on polymorphic microsatellites has been used worldwide in parentage determination, while the low mutation rate and genotyping error rate of single nucleotide polymorphisms (SNPs) make them another important marker for pedigree tracing. Here, we compared the effectiveness of microsatellites and SNP m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 33 publications
(31 reference statements)
0
14
0
2
Order By: Relevance
“…If we limit the overview to vertebrates alone, we can distinguish different types of research. Some studies have compared the effectiveness of the two markers: (i) for the purpose of performing kinship analyses [9][10][11][12][13], (ii) to infer diversity parameters e.g., [14,15], and (iii) to analyze genetic relationships between populations [16][17][18][19][20]. This last group is of particular interest for this study as it aims to enrich knowledge about the precise issue of the inference of population genetic structure.…”
Section: Introductionmentioning
confidence: 99%
“…If we limit the overview to vertebrates alone, we can distinguish different types of research. Some studies have compared the effectiveness of the two markers: (i) for the purpose of performing kinship analyses [9][10][11][12][13], (ii) to infer diversity parameters e.g., [14,15], and (iii) to analyze genetic relationships between populations [16][17][18][19][20]. This last group is of particular interest for this study as it aims to enrich knowledge about the precise issue of the inference of population genetic structure.…”
Section: Introductionmentioning
confidence: 99%
“…The study indicated that the number of SNP loci required was also related to the species population size of the estimated model. When the population was larger, the number of SNP loci required to meet the accuracy requirements of the identification was higher (Turakulov and Easteal 2003;Yu et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Parentage analysis and parentage verification are very important for an efficient genetic management in livestock breeding (Yu et al, 2015). Traditionally, pedigree records are the foundation of the breeding programs, but if this records are incomplete or inaccurate, these data can lead to unexpected and undesired consequences and errors in further breeding.…”
Section: Introductionmentioning
confidence: 99%